Poverty: a matter of human rights (Legal journal - Research in Legal and Social Sciences, 2018)
An awful truth burdens on a great part of America ́s population, consigned to poverty, if not extreme poverty. That is a human rights matter, rather than economic, since this situation reveals, on one hand, the violation of several rights, if not all, recognised by human rights law, and on the other hand the non-compliance of the obligations contracted by the States within the mentioned law ́s framework. This raises the commitment of men and women dedicated to law, to know if juridical knowledge is what it has to be: a knowledge that advocates for people ́s liberationfrom the injustices that keep them from developing all of their potentiality and excellence. One of the tools to achieve that, is justiciability of human rights, and veryspecially, economic, social and cultural rights, mainly when among the measures to be observed in terms of the mentioned international obligations, there are court sentences.
Keywords: poverty; human dignity; economic; social and cultural rights; justiciability